Consumption Patterns of Animal and High Fat Food Items by Patients with Coronary Artery Disease (CAD) - Bandara, E.M.S.; Ekanayake, S.; Kapuruge, A.D.; Wanigatunge, C.A. (University of Ruhuna, Matara, 2015)
Coronary Artery Disease (CAD) is a leading cause of premature deaths in Sri Lanka. Blood lipid abnormalities, hypertension, diabetes, and obesity are some of the modifiable risk factors of CAD. Poor dietary habits are recognized as a major contributor in the development of such modifiable risk factors. The objective of this study was to examine animal (chicken, red meat, fish and egg with yolk) and high fat food (full cream milk powder, fast food) consumption patterns of patients with CAD. Patients (n=87) from a selected center who were to undergo CABG participated in the study. Patients' awareness of their dyslipidemic condition, and animal and high fat food consumption frequency (≥3 times per week and < 3 times per week) were recorded by using an interviewer administered questionnaire. Dyslipidemic conditions of the patients were obtained from the bed head tickets. The severity of CAD was evaluated by Genisini score. The sample was divided in to two groups as those who were aware of dyslipidimic condition (group A, n=61) and those who were not aware of dyslipidemic condition, but were under the treatment of lipid lowering drugs (group B, n=26). In group A, the prevalence of consumption (≥3 times per week) of red meat, chicken, fish, egg with yolk, fast food and full cream milk were 21 %, 20%, 59%, 21 %, 52%, and 96% respectively. The corresponding figures for group B were 40%, 24%, 78%, 65%, 57%, and 90%. There was a significant difference (X2= 9.9, p<0.01) in consumption of egg between the two groups. Even though no significant difference was observed, in the Genisini score, it was high in group B (those who were unaware of dyslipidemia). Consumption of ≥ 3 times per- week of red meat, chicken, fish, egg with yolk and fast food were higher in group B compared to group A. Therefore, consumption of foods suitable for dyslipidemic condition may contribute to reduce the severity of the CAD condition.
Acknowledgements: National Science Foundation (Grant NSF/RG/2011/HS/18), Staff Cardio Thoracic Unit, Sri Jayewardenepura General Hospital)
Keywords: Coronary Artery Diseases; Dietary habits